Benefícios sociais e ambientais do coprocessamento de pneus inservíveis: estudo de caso na cidade de João Pessoa-PB - Freitas, Sidcléa Sousa de (2010)
The useless tire is a residue that must be managed correctly until its final disposal as well as its collection and storage must be done adequately. Therefore, if it is inadequately disposed of, it can cause damages to the environment and to public health. In March 2005 the city of João Pessoa, initiated a program called Programa Nordeste Rodando Limpo - Northeastern Program of Clean Twirling - through the partnership between private companies, which consisted of the collection and final destination of the useless tires to be used in the ovens to produce clinker, providing a market value to these residues. This research was developed at CIMPOR, a cement plant located in the city of João Pessoa and has as its objective to make an analysis of the main benefits of the use of theses tires during the co-processing step inside the clinker oven. The methodology applied in this study were based on the qualitative evaluation of the generated benefits to public health and the quantitative social profits generated to the recycling workers and identifying profits with the collection of the tires as well as the increasing of the these workers income. The same research also verified that the co-processing atmospheric emissions and CO2 emissions were prevented during the transportation of the Petroleum coke. This also lessened the involved costs with this process. In all cases, the final results had confirmed the existence of environmental and social benefits in the use of the co-processing system, making possible the withdrawal of 26.568, 90 tons of useless tires that were deposited in the State of Paraiba. Consequently, in neighboring states, it was also verified the automatic creation of a mechanism of collection by the society that made possible economic profits of an estimated R$ 2 million reais to the recycling workers improving their quality of life. Another important data observed in the same study was a gradual increase of the use of useless tires, implying in a lesser consumption of non renewable fuel and the minimization of atmospheric emissions which prevents high levels of CO2 emissions, generally caused by the lesser volume of Petroleum coke produced, also resulting, in the decrease of the production costs.